Sex-related differences in the response of anti-platelet drug therapies targeting purinergic signaling pathways in sepsis - Amoafo, Emmanuel Boadi; Entsie, Philomena; Albayati, Samara; Dorsam, Glenn P.; Kunapuli, Satya P.; Kilpatrick, Laurie E.; Liverani, Elisabetta (Frontiers in Immunology, 2022)
Sepsis is a major healthcare problem associated with high mortality. Differences in the immune response to sepsis have been proposed and they may determine responses to therapeutic interventions. Purinergic signaling is a novel sex-specific regulatory mechanism in immune cells physiology and activation. It is unclear whether sex-related differences in targeting purinergic signaling during sepsis. Our studies have shown that targeting the ADP-receptor P2Y12 but not P2Y1 was protective in male mice during sepsis, and we now hypothesis that there are sex-related differences in modulating P2Y12 or P2Y1 signaling pathways during sepsis. Male and female wild type (WT), P2Y12 knock-out (KO) and P2Y1 KO mice underwent sham surgery or cecal ligation and puncture (CLP) to induce sepsis. The P2Y12 antagonist ticagrelor or the P2Y1 antagonist MRS2279 were administered intra-peritoneally after surgery to septic male and female mice. Blood, lungs and kidneys were collected 24 hours post-surgery. Sepsis-induced changes in platelet activation, secretion and platelet interaction with immune cells were measured using flow cytometry. Neutrophil infiltration in the lung and kidney was determined by myeloperoxidase (MPO) activity. Sepsis-induced platelet activation, secretion and aggregate formation were significantly reduced in male CLP P2Y12 KO and in female CLP P2Y1 KO mice compared with their CLP WT counterpart. Sepsis-induced MPO activity was reduced in male CLP P2Y12 KO and CLP P2Y1 KO female. CLP males treated with ticagrelor or MRS2279 showed a significant decrease in MPO levels in lung and kidneys as compared to untreated male CLP mice. In CLP male mice treated with ticagrelor or MRS2279 there was a significant decrease in circulating sepsis-induced aggregate formation as compared with untreated male CLP. Sepsis-induced platelet activation was significantly reduced in male mice treated with ticagrelor but not MRS2211 as compared with the untreated male CLP. There were no differences in platelet activation, aggregate formation and neutrophil infiltration in lung and kidney between female CLP mice and female CLP mice treated with ticagrelor or MRS2279. In conclusion, targeting purinergic signaling represents a promising therapy for sepsis but drug targeting purinergic signaling is sex-specific and they need to be investigated to determine sex-related targeted therapies in sepsis.